Competing Matchmakers: An Experimental Analysis - Hossain, Tanjim; Minor, Dylan; Morgan, John (Management Science, 2011)
Platform competition is ubiquitous, yet platform market structure is little understood. Theory models typically suffer from equilibrium multiplicity—platforms might coexist or the market might tip to either platform. We use laboratory experiments to study the outcomes of platform competition. When platforms are primarily vertically differentiated, we find that even when platform coexistence is theoretically possible, markets inevitably tip to the more efficient platform. When platforms are primarily horizontally differentiated, so there is no single efficient platform, we find strong evidence of equilibrium coexistence. This paper was accepted by Peter Wakker, decision analysis.